Microplastic contamination in marine ecosystem of peninsular Malaysia: a review in marine water, sediment, and marine fish - Ezraneti, Riri; Hassan, Noor Artika; Miskon, Mohd Fuad; Mohamed, Juliana (Oriental Scientific Publishing Company, 2024)
This study discusses the numbers, types, shapes, and sizes of microplastics (MPs) in marine surface waters, sediments, and marine fish in Peninsular Malaysia. Research publications were gathered and organized utilizing Google Scholar, Science Direct, and Springer Link from 2015 to 2024. The review findings indicate a lack of evidence about microplastic contamination in Kelantan, Perlis, Johor, and Melaka, highlighting the necessity for more research in these regions. Moreover, research on microplastics in surface waters, sediments, and marine life, including fish, requires the standardization of methodologies and equipment. Currently, investigations on microplastics in fish flesh are still limited and require more studies concerning human health risk assessment. Ultimately, focused mitigation strategies and comprehensive research through the development of standardized equipment and methodologies are required to assess microplastic contamination in the marine environment to protect marine ecosystems and humans, particularly in Peninsular Malaysia.